Knowledge and attitude among night market food operators toward food waste management practices: a conceptual paper/ Muhammad ‘Arif Aizat Bashir - Bashir, Muhammad ‘Arif Aizat; Abd Majid, Hairul Nizwan; Alden, Sperico Michael; Hussin, Shahril; Mohd Shah, Mohd Redzuan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
As a developing country, Malaysia is facing the challenge of economic growth and rapid expansion; and waste generation is one of the drawbacks of it. Plenty of tons of food waste is found in the landfill of Malaysia. The Solid Waste Management and Public Cleansing Corporation (SWCorp) stated about 40 percent of solid waste that is being produced daily constitutes food waste. It is found that one of the highest contributors to food waste in Malaysia is night market. In line with the above notion, it is proposed that knowledge and attitude has a positive relationship toward proper waste management practices among night market food operators. Therefore, this paper is intended to conceptualize the knowledge and attitude among night market food operators toward food waste management practices.